Pengaruh Harga dan Kepercayaan Terhadap Brand Image Klinik Pratama ST. Agustinus Fatubenao Nusa Tenggara Timur - Sherlyn Puspitasari; A. Rohendi; Rian Andriani (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Price plays a significant role in attracting consumers to repeatedly visit a healthcare clinic. Consumer trust in the services provided by healthcare professionals encourages them to return to the clinic. This, in turn, can enhance the clinic's Brand Image. St. Agustinus Fatubenao Primary Clinic in East Nusa Tenggara is one of the clinics in a remote area with a relatively low Brand Image, and it is facing increasing competition from other clinics in the area. The objective of this research is to examine the impact of price on Brand Image, the impact of trust on Brand Image, and the simultaneous effect of price and trust on Brand Image. The research population consists of all consumers who have used the services at St. Agustinus Fatubenao Primary Clinic in East Nusa Tenggara within the last year. The sampling technique used is purposive sampling with a sample size of 90 individuals. This research adopts a quantitative approach with a correlational research design. The research instrument is a questionnaire using a Likert scale, and quantitative data analysis is performed using IBM SPSS 20 software. The research findings show that price and trust have a combined effect on Brand Image of 60.3%, while the remaining 39.7% is influenced by other variables or factors that are not comprehensively covered in the study.